Corrosion Rate of ASTM A53 Steel in Seawater Influenced by Variation in Concentration of Mangifera Indica L. Peel Extract - Selly Septianissa; Ayu Zahra Chandrasari (Journal of Applied Engineering and Technological Science (JAETS), 2024)
This study investigates the effectiveness of mango peel extract as a corrosion inhibitor for ASTM A53 steel, which is widely used in the oil and gas industry. The research aims to evaluate how different concentrations of mango peel extract can mitigate corrosion in seawater from Pangandaran, thereby extending the lifespan of steel components in marine environments. Corrosion tests were conducted through immersion experiments over durations of 1, 4, 9, 16, and 25 days with mango peel extract concentrations of 0 ppm, 20 ppm, 40 ppm, 60 ppm, and 80 ppm. Analytical methods including X-ray diffraction (XRD), Optical Microscopy (OM), energy dispersive spectroscopy (EDS), and scanning electron microscopy (SEM) were used to examine the steel's surface morphology and chemical composition. The results demonstrate that mango peel extract significantly reduces the corrosion rate of ASTM A53 steel, with the highest efficiency achieved at 40 ppm (58.15%) and a notable reduction at 60 ppm (56.4%). The inhibition is attributed to chemical absorption, which lowers the steel's corrosion potential. These findings suggest that mango peel extract is an effective, eco-friendly corrosion inhibitor, offering practical and theoretical benefits for corrosion management. This research supports the use of bio-based inhibitors and may inform future industrial corrosion protection strategies.